'I Wouldn't Have What It Takes': Young Swedes' Understandings of Political Participation. (May 2016) - Sveningsson, Malin
Research on young people and citizenship has often depicted those who do not participate in manifest political contexts as 'passive'. However, the space between 'active' and 'passive' is complex and hosts a number of different positions. Using a qualitative mixed methods approach, this article provides insights into how a group of young people, who can be described as 'standby citizens' (Amnå & Ekman, 2014), perceive political participation, and ultimately, why they, despite a strong interest in politics, are reluctant to describe themselves as 'politically engaged'. Eight themes were identified and grouped into three categories focusing on different aspects: What forms engagement should take in order to count as such, what characteristics engaged persons were perceived to have and what political engagement was perceived to be about. All three contributed towards making the position 'politically engaged' difficult to claim, but also somewhat undesirable, for the participants.